THE INFLUENCE OF BABY GYMNASTICS ON BABY DEVELOPMENT AGES 6-9 MONTHS - Siti Patimah; Tavazuli Clara; Herni Kurnia (Midwifery and Nursing Research, 2021)
Background: The future of a nation depends on the success of children in achieving optimal growth and development. Good and sufficient nutrition, good health status, proper parenting, and proper stimulation will help children to develop optimally. Efforts to stimulate children's development, including by doing gymnastics in infancy. Proper stimulation will stimulate the brain so that the development of movement, speech and language, social and independence abilities takes place optimally according to age. This study aims to analyze the effect of the application of baby gymnastics on the development of infants aged 6-9 months in the Panglayungan Public Health Center, Tasikmalaya City..Methods: This study used a quasi-experimental method and pre-post test only group design.The number of samples was 19 people. Each respondent was screened for development before and after being given baby gymnastics treatment for 1 month.Results:The description of the development of infants aged 6-9 months in the work area of the Panglayungan Health Center, Tasikmalaya City before stimulation with baby gymnastics had an appropriate development of 73.7% and 26.3% doubtful. After stimulation with baby gymnastics, 100% of babies reach development according to their age, showed by the p value 0,000.Conclusion: Based on the results of the study, it was found that there was an effect of baby gymnastics on the development of infants aged 6-9 months